PENDIDIKAN SENI TARI SEBAGAIPendidikan Seni Tari sebagai Alternatif Pendidikan Multikultur bagi Siswa SD ALTERNATIF PENDIDIKAN MULTIKULTUR BAGI SISWA SD - Non Dwishiera Cahya Anasta (Universitas Pendidikan Indonesia (UPI), 2021)
Dance art is a work of art that contains a cultural encyclopedia. Traditional dance in Indonesia is a representation of multicultural Indonesian society, because traditional dance represents philosophical messages, both in the spiritual, moral and social aspects of the supporting community. This article examines how dance education has benefits for multicultural education for elementary school children. The aim is to explain the meaning of cultural diversity as something that is beneficial for the lives of local, national and global communities. Through dance education in elementary schools, students can be creative and appreciate the art of Indonesian dance. So it is expected that elementary students will know the treasures of their own nation's dance, as well as learn about the cultural differences between regions. Thus, they will become individuals who are able to respect differences and diversity, and accept the reality of the plurality of cultures that exist in Indonesia